The effects of overeducation on multiple job satisfaction towards enhancing individuals‘ well-being in Malaysia / Zainizam Zakariya and Harminder Battu - Zakariya, Zainizam; Battu, Harminder (Faculty of Business Management, 2013)
The aim of this paper is to examine the effects of overeducation on workers‘ job satisfaction towards enhancing individuals‘ well-being in Malaysia. Based upon 41,495 graduates from the 2007 Graduate Tracer Study (GTS-07) in Malaysia was analysed using subjective method of a worker‘s own assessment approach and logit model regression. Four multi-dimensions of satisfaction used here- high self-satisfaction, valuable work experience, anything can be learnt for the job occupied and job challenging. The study found that 32% of workers were overeducated - moderately overeducated (22%) and severely overeducated (10%). The logit model suggests that overeducation decreased individuals‘ job satisfaction across the four job satisfaction dimensions. This negative effects are much higher for high self-satisfaction and for the workers who are severely rather than moderately overeducated. This paper is perhaps one of the first to address the effects of overeducation in Malaysia which remains to be very scarce in the context of any developing country. To improve workers‘ well-being, individuals must find a job for which their educational backgrounds are required for the job they are doing.